Peran Guru Penggerak Dalam Mmeningkatkan Kualitas Pendidikan: (Suatu Tinjauan Terhadap Kurikulum Mardeka Belajar di SMA Negeri 2 Ende tahun 2023/2024) - Maria Gleofariska Meo (Program Studi Pendidikan Ekonomi FKIP Universitas Flores, 2024)
This research aims to know and describe (1) the role of driving teachers in SMA Negeri 2 Ende, (2) the quality of education at SMA Negeri 2 Ende. This research uses a qualitative research type. The data collection techniques used are (1) Interviews, (2) Observation, and (3) Documentation. The research subjects in this study were 3 people, namely 2 driving teachers and the principal of SMA Negeri 2 Ende. Data analysis techniques use the Miles and Huberman model. (1) Driving teachers act as leaders in learning. The roles carried out are making agreements with students about good things to do; As a driver of the practical teacher community, driving teachers have formed a learning community in the school and registered on the Merdeka Mengajar platform; As a mentor, driving teachers have been active in guiding and facilitating other teachers in developing teaching modules that suit the needs of students; As a driver of collaboration and cooperation among teachers, and driving teachers at SMA Negeri 2 Ende have played a good role as a spirit giver for teachers in increasing the enthusiasm for learning; As the embodiment of student leadership, driving teachers play a role in initiating and encouraging the implementation of project-based learning amongr teachers. (2) SMA Negeri 2 Ende has shown good quality education, as evidenced by the determination of grade promotion and grade promotion that refers to the SMNP.